Dynamics and an Optimal Policy for A Discrete Time System with Ricker Growth - Hamoudi, Ghosoon M.; Al-Nassir, Sadiq (Iraqi Journal of Science, 2019)
The goal of this paper is to study dynamic behavior of a sporadic model (prey-predator). All fixed points of the model are found. We set the conditions that required to investigate the local stability of all fixed points. The model is extended to an optimal control model. The Pontryagin's maximum principle is used to achieve the optimal solutions. Finally, numerical simulations have been applied to confirm the theoretical results.